Mission and Reconciliation in the Orthodox Church: From Busan (2013) to Karlsruhe (2022) - Basileiadēs, Petros Bas. (International review of mission, 2020)
This article examines the Orthodox view on reconciliation as reflected in the famous patriarchal and synodical encyclicals early in the last century and in more recent official documents: the Messages of the Primates of the Orthodox Churches, the approved documents of the Holy and Great Council of the Orthodox Church, and Ecumenical Patriarch Bartholomew’s official statements. These are looked at in reference to (i) the mission statement of the Commission on World Mission and Evangelism, Together towards Life, and (ii) the papal encyclicals Unitatis redintegratio and Ut unum sint. The article further examines the need for a common Christian witness and the reactions within the Orthodox world from a tiny but vocal anti-ecumenical minority. It underlines the importance of a Universal Declaration of Human Responsibilities along with the existing Universal Declaration of Human Rights to address the ecological problem and inequities of the current world economic system, based on the interrelatedness of economy and ecology and the consolidation of the interfaith dialogue for a wider reconciliation. The article also underlines the highest priority of the theological dialogues at all levels and by all bodies of the Orthodox ecclesial reality as a necessary step to promote reconciliation. Finally, the article assesses (i) the dialogue aiming to achieve the visible unity of the church; (ii) dialogues generally focusing on Christian unity, or even unity with other faithful; (iii) dialogues aiming as much as possible at common Christian witness; and (iv) dialogues focusing on the church’s responsibility toward society and the integrity of creation.